Toward Nontransient Silk Bioelectronics: Engineering Silk Fibroin for Bionic Links. Issue 10 (29th June 2020) - Patil, Anoop C.; Xiong, Ze; Thakor, Nitish V.
Abstract: Silk fibroin holds promise a new generation of soft bioelectronics due to its excellent biocompatibility, tailorable biodegradability, and an impressive set of mechanical properties. Silk can be expressed in different material forms, providing many options for integrating silk with implantable sensors and devices. So far, silk has mainly driven the development of resorbable interfaces for in vivo applications. However, the pursuit of nontransient (water‐stable) silk bioelectronics is interdisciplinary, requiring unconventional techniques for integrating silk with thin sensing and conducting materials in a non‐resorbable package. This convergence of need, know‐how, and the potential impact on implantable applications point to the huge potential of silk in refashioning the field of bionic links. This report begins with a general overview of the bionic link, defined as the electronic link between the biological (neural) tissue and the interface electronics. Then, the prominent trends in the use of silk fibroin for designing bionic links (inclusive of transient sensors and devices, and soft conformal nontransient tissue interfaces), key fabrication strategies, and applications are analyzed, followed by a highlight of the material aspects driving the maturity of nontransient silk fibroin technology for implantable bioelectronics. Abstract : Nontransient silk bioelectronics holds promise for a new generation of soft and excellently biocompatible implantable devices. Silk fibroin has so far championed the design of resorbable bioelectronic interfaces inside the body. The push for nontransient silk implantable devices and their reliable and scalable manufacturing is an interdisciplinary pursuit, inclusive of materials science challenges, and unconventional microfabrication, interconnect and encapsulation strategies.